Pharmacognostic Standardization of Stevia rebaudiana and its HPLC Quantification for Stevioside as Sweetening Compound - Reshma Sawant; Kopparam Manjunath; Siddalingappa Bhagawati; Rashmi Surve; Neha Shivathaya (RGUHS Journal of Pharmaceutical Sciences)
Background Stevia rebaudiana a perennial plant is renowned for its pleasant sweet-tasting leaves. Many people use it as a natural sweetener. Accurate pharmacognostic evaluation besides compound quantification is vital for standardizing its medicinal and commercial applications.Objectives This study aimed to evaluate the pharmacognostic features of S. rebaudiana leaves and quantify a key compound in its extract using a calibration curve to evaluate accuracy and sensitivity.Methods The leaves of S. rebaudiana were collected authenticated and subjected to macroscopic micro-scopic and powder microscopy analysis. Leaf constants and ash values were determined. Phytochemical screening was performed to detect significant constituents. A calibration curve was constructed with standard solutions 10-50 mugml yielding a linear relationship rsup2 0.999. The extractrsquos component concentration peak area and retention duration were measured using high-performance liquid chromatography HPLC.Results Pharmacognostic analysis revealed key diagnostic features including epidermal cells glandular trichomes stomata and vascular tissues. Phytochemical screening identified carbohydrates proteins glycosides flavonoids alkaloids tannins and phenols without steroids. The calibration curve demonstrated excellent linearity the compounds retention time was 5.165 minutes. The concentration of stevioside in the extract was calculated to be 11.35 mugml.Conclusion The study confirmed the identity purity and quality of S. rebaudiana through pharmacognostic evaluation and validated the reliability of the quantification method. These results support using Stevia in standardized herbal preparations and as a natural sweetener.